PENGARUH SOSIALISASI PAJAK, KESADARAN WAJIB PAJAK, KEBIJAKAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI SURAKARTA - Djoko Kristianto, Claudita Putri, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
The aim of this research is to analyze tax socialization, taxpayer awareness, tax policy, and tax penalty towards individual taxpayer compliance. The research uses quantitative data. The data source uses primary data. The data collecting technique uses questionnaires. The sampling technique uses accidental sampling and samples of 100 respondents. The data analysis techniques are classical assumption test, multiple linear regression analysis, F test, t test, and coefficient of determination test. The test result shows that the tax socialization gives a significant and positive effect towards individual taxpayer compliance. The tax penalty gives an insignificant positive effect towards individual taxpayer compliance. Keywords: tax socializtion, taxpayer awareness, tax policy, tax penalty, individual taxpayer compliance